Refugees, food security, and resilience in host communities: Transitioning from humanitarian assistance to development in protracted refugee situations - Mabiso, Athur; Maystadt, Jean-François; Vandercasteelen, Joachim; Hirvonen, Kalle (International Food Policy Research Institute, 2014)
An emerging literature shows how the mass arrival of refugees induces both short- and long-term consequences to hosting countries. The main contribution of this paper is to conduct a selective review of this literature from a food-security and resilience perspective. First, the paper identifies a number of direct and indirect food-security consequences of hosting refugees. It provides a conceptual framework for discussing these various channels through which refugee inflows influence food security in the hosting countries. Second, the literature review finds that the impact of large-scale influxes of refugees on host communities and on their food security is unequally distributed among the local population.